KNOWING SELF, IDENTITY, AND OTHERNESS: An Epistemological Account after Aquinas and Wittgenstein - Paikkattu, Vinoy Thomas (Journal of Dharma, 2018)
In a closer scrutiny, discussions on the self, identity, and the other take an epistemological turn in Aquinas and Wittgenstein. Both of them leave ample space for it notwithstanding their ontological and linguistic philosophies, respectively. The epistemology that can be drawn from them does not limit itself to the ‘process of knowledge’, rather moves beyond the synthesis of knowledge to the integration of life and actions. The dichotomy between ‘self’ and the ‘other’ and the ‘inner’ and the ‘outer’ are overcome with the relational epistemology. Systemic epistemology is transformed to relational epistemology where relationality of knowing, acting, and being constitute a linguistic community. Human persons as the members of this community play distinct roles in the human world where other beings also exist.